Recent advances in lead-free based perovskite solar cells on optoelectronic properties, stability and economic feasibility. (27th September 2022) - Chakraborty, Kunal; Gupta Choudhury, Mahua; Choudhury, Sushabhan; Paul, Samrat
Abstract: The present review article represents the scope of different lead (Pb)-free hybrid halide Perovskite solar cells (PSC) for photovoltaic (PV) applications. Research on lead-free material is emerging mainly to identify the alternatives of lead in the Perovskite solar cells. Several homovalent (Sn 2+, Ge 2+, Cu 2+ ) and heterovalent (Sb 3+, Bi 3+, Ti 4+ ) materials have good physical properties to replace the lead content in the absorbing material compound. However the power conversion efficiency (PCE, %) is not higher as compared to lead based material. This review article focuses on the characteristics, material properties, stability and performance of the different Pb-free materials as absorbing layer in the Perovskite solar cells.